Dynamic Response Analysis of the Cracked Fault Gear System Based on the Finite Element Model - Jiao Wei; Xu Kejun; Qin Haiqin (Jixie chuandong)
In order to better reveal the influence of tooth root crack failure on the dynamic characteristics of the gear system, the whole process of failure mechanism analysis—gear system modeling—crack failure test is carried out. Firstly, considering the more realistic tooth root transition curve and effective tooth thickness reduction limit line, a more rigorous crack gear tooth model is established, the meshing stiffness calculated by the traditional potential energy method is improved, and the stiffness of 6 kinds of cracks with different depths is studied. Secondly, in view of the shortcomings of the traditional lumped parameter model, a finite element dynamic model of the gear-rotor system is established based on the Timoshenko beam element theory. Finally, the Newmark-β method is used to solve the dynamic response of the gear system with normal/different depth crack faults, and compared with the experimental results considering the influence of rotational speed. The results show that when there is a crack in the tooth root, the acceleration response has a periodic impact characteristic, and the side frequency phenomenon in the frequency domain occurs near the meshing frequency and its harmonics; the strength of impact components in both the time and frequency domains is positively correlated with crack depth and rotational speed. The simulation results and the measured signals show consistent characteristics, which verify the correctness of the method in this study.